Algumas características físicas, químicas e de fertilidade de uma amostra de solo da Antártida - Alvarez V, Victor Hugo; Dias, Luiz Eduardo (Revista Ceres, 2025)
A sample of soil collected near the Comandante Ferraz Station, King George Island, on the Antarctic Ice Pack, was evaluated for chemical and physical properties and nutrient availability compared with 2 typical cerrado Latossols using the Neubauer biological test.